Preliminary Interpretation of the Induction Period in Hydration of Sodium Hydroxide/Silicate Activated Slag - Zuo, Yibing (Materials (Basel), 2020)
Many calorimetric studies have been carried out to investigate the reaction process of alkali-activated slag paste. However, the origin of the induction period and action mechanism of soluble Si in the dissolution of slag are still not clear. Moreover, the mechanisms behind different reaction periods are not well described. In this study, the reaction kinetics of alkali-activated slag paste was monitored by isothermal calorimetry and the effect of soluble Si was investigated through a dissolution test. The results showed that occurrence of the induction period in hydration of alkali-activated slag paste depended on the presence of soluble Si in alkaline activator and the soluble Si slowed down the dissolution of slag. A dissolution theory-based mechanism was introduced and applied to the dissolution of slag, showing good interpretation of the action mechanism of soluble Si. With this dissolution theory-based mechanism, origin of the induction period in hydration of alkali-activated slag was explicitly interpreted.